Comparison of two rating scales with the orofacial esthetic scale and practical recommendations for its application - Swaha Pattanaik; Mike T. John; Seungwon Chung; San Keller (Health and Quality of Life Outcomes, 2022)
Abstract Purpose We compared measurement properties of 5-point and 11-point response formats for the orofacial esthetic scale (OES) items to determine whether collapsing the format would degrade OES score precision. Methods Data were collected from a consecutive sample of adult dental patients from HealthPartners dental clinics in Minnesota (N = 2,078). We fitted an Item Response Theory (IRT) model to the 11-point response format and the six derived 5-point response formats. We compared all response formats using test (or scale) information, correlation between the IRT scores, Cronbach’s alpha estimates for each scaling format, correlations based on the observed scores for the seven OES items and the eighth global item, and the relationship of observed and IRT scores to an external criterion using orofacial appearance (OA) indicators from the Oral Health Impact Profile (OHIP). Results The correlations among scores based on the different response formats were uniformly high for observed (0.97–0.99) and IRT scores (0.96–0.99); as were correlations of both observed and IRT scores and the OHIP measure of OA (0.66–0.68). Cronbach’s alpha based on any of the 5-point formats (α = 0.95) was nearly the same as that based on the 11-point format (α = 0.96). The weighted total information area for five of six derived 5-point response formats was 98% of that for the 11-point response format. Conclusions Our results support the use of scores based on a 5-point response format for the OES items. The measurement properties of scores based on a 5-point response format are comparable to those of scores based on the 11-point response format.